Effect of compressive strength on impact energy for fly ash concrete - Padmanaban, I.; Kandasamy, S. (Journal of Structural Engineering, 2024)
Concrete Structures designed for static loads are also subjected to accidental or deliberate impact or blast loads because of industrial or transportation accidents, military or terrorist activities. Such structures require realistic assessment of the ultimate impact resistance and a mode of failure of the structure. This paper presents the study of impact characteristics of Indian fly ash mixes with locally available ingredients. Impact study was conducted by means of drop weight test method to evaluate the properties like impact energy absorbed, impact energy efficiency of cement and effect of compressive strength on impact strength with ages. The results of the investigations shows that Indian fly ash can be effectively utilizedfor improving impact characteristics of concrete structures.